Perancangan Sistem Informasi Akuntansi Persediaan Barang Dagang Pada Cv Sumatera Ev Berjaya Palembang - Siahaan, Rafael Michael Manasye; Sari, Yuliana; N, Nurhasanah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
CV Sumatera EV Berjaya is a trading company engaged in the sales of electric bicycles and related components. In its operational activities, inventory recording is still conducted manually using Microsoft Excel, which is prone to errors and discrepancies between recorded and physical stock data. This final report aims to design an accounting information system for inventory using Accurate Accounting Software to enhance accuracy and efficiency in inventory management. The author employed data collection methods such as observation and interviews with company personnel. The system design results show that Accurate supports item data input, transaction recording, and report generation in an integrated and real-time manner. A comparison between the manual system and Accurate demonstrates that the computerized system significantly reduces data entry errors, accelerates stock checking processes, and improves decision-making effectiveness. This report is expected to serve as a reference for implementing appropriate accounting information systems for inventory in similar trading companies.